An Implementation of Error Minimization Data Transmission in OFDM using Modified Convolutional Code - Briantoro, Hendy; Astawa, I Gede Puja; Sudarsono, Amang (Politeknik Elektronika Negeri Surabaya (PENS), 2015)
This paper presents about error minimization in OFDM system. In conventional system, usually using channel coding such as BCH Code or Convolutional Code. But, performance BCH Code or Convolutional Code is not good in implementation of OFDM System. Error bits of OFDM system without channel coding is 5.77%. Then, we used convolutional code with code rate 1/2, it can reduce error bitsonly up to 3.85%. So, we proposed OFDM system with Modified Convolutional Code. In this implementation, we used Software Define Radio (SDR), namely Universal Software Radio Peripheral (USRP) NI 2920 as the transmitter and receiver. The result of OFDM system using Modified Convolutional Code with code rate is able recover all character received so can decrease until 0% error bit. Increasing performance of Modified Convolutional Code is about 1 dB in BER of 10-4 from BCH Code and Convolutional Code. So, performance of Modified Convolutional better than BCH Code or Convolutional Code.Keywords: OFDM, BCH Code, Convolutional Code, Modified Convolutional Code, SDR, USRP